Privacy Management in the Digital Era: Managing Instagram Close Friends Feature Among Lampung University Students - Azis, Diky Luqman; Windah, Andi; Nurhaida, Ida (KOMUNIKA, 2024)
Concerns about personal information leakage have been growing alongside the ease with which personal data is shared on social media platforms. Instagram's "Close Friend" feature offers users greater control over their privacy. Interestingly, many users continue to utilize this feature on their second accounts, despite these accounts already being populated with close friends and trusted individuals. This study aims to explore how individuals manage their personal information privacy through the use of the Close Friend feature on their second accounts Instagram, using the Communication Privacy Management (CPM) theory. The research adopted a quantitative approach with a sample of 100 respondents selected through purposive sampling. Data was collected using questionnaires and analyzed using Smart PLS 4.0. The results indicate that communication privacy management has a strong relationship with the use of the Close Friend feature on second accounts, with an R-square value of 70.5%, suggesting a significant influence. These findings reveal that even when users' second accounts consist of trusted individuals, they still choose to limit the information shared with a smaller group to protect their privacy. This study provides insights into how social media users manage privacy by selectively sharing personal information through platform features.